Numerical Simulation of Sloshing in a Spherical GPL Storage Tank - Nunes, Bernardo Miguel Pires dos Santos (2023)
In recent years, due to the evolution of computational resources, it has been possible to start the computational investigation of the influence of NATECH accidents (Natural Hazards Triggering Technological accidents) on the infrastructures of the oil industry. NATECH often represents situations not contemplated in the standards, which makes the application of numerical methods a complementary strategy to construction design. The objective of this dissertation is to study the sloshing phenomenon in a spherical Propane tank of CLC - Companhia Logística de Combustíveis, when it is subjected to a seismic signal. Sloshing is the consequence of a transient regime imposed on the boundaries of the tank, especially when there is a free surface. This condition, in turn, can create an imbalance in the forces that are normally not included in the construction design. Numerical simulations were developed using a finite volume program (ANSYS-Fluent). The RANS equations were solved with the − turbulence model, and the free surface was modeled with the VOF (Volume of Fluid) method. The numerical model proved capable of simulating the deformation of the free surface inside the tank. From the numerical results obtained, it was concluded that the numerical model accurately simulates the flow field, with the solution of the deformed free surface having a high gradient, which requires a very refined mesh. The study of mesh independence showed that, in this situation, the mesh must be smaller than 125 mm for the tank of 16 meters in diameter.